1967
DOI: 10.1351/pac196715010123
|View full text |Cite
|
Sign up to set email alerts
|

Inert carbon free radicals

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 1 publication
0
37
0
Order By: Relevance
“…6 Together, these studies have been regarded as both promising and significant. 5 As a result, the synthesis of perchlorinated trityl radical has become an immense undertaking with promising implications.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Together, these studies have been regarded as both promising and significant. 5 As a result, the synthesis of perchlorinated trityl radical has become an immense undertaking with promising implications.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Studies have also shown that these reactive radicals become stable and chemically inert upon perchlorination. [5][6][7][8] In light of this endeavor, highly chlorinated mono-, di-, and triarylmethanes were developed and since then they have become the most valuable chemical precursors of inert free radicals with estimated half-lives in the order of 100 years. 6 Together, these studies have been regarded as both promising and significant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The so-called 'inert carbon-free radicals' belong mainly to the perchlorodiphenylmethyl (Ballester & Riera, 1954), perchlorotriphenylmethyl (Ballester, 1967;Ballester, Riera, Castafier, Badfa & Mons6, 1971) and 9-phenylfluorenyl radical (Ballester, Castafier & Pujadas, 1971) classes. They have chemical and thermal stabilities which are higher than those of the majority of normal tetrahedral carbon compounds and materials.…”
Section: Commentmentioning
confidence: 99%
“…18,23 Another family of trityl radicals, the tetrachloro-TAM radicals, was first introduced in 1967 (see Figure 1B). 24 Upon substitution of the six ortho positions with chlorine atoms, the central methyl carbon was sterically shielded providing high chemical and thermal stability. 25,26 Tetrachloro-TAM radicals show broader EPR lines due to coupling with the chlorine nuclei in close vicinity, but are distinguished by better synthetic accessibility than tetrathiatrityl radicals.…”
Section: Introductionmentioning
confidence: 99%